UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS DENGAN BERMAIN LEGO KONSTRUKTIF PADA ANAK KELOMPOK A PAUD RAUDATUL JANNAH DESA GENGGELANG KECAMATAN GANGGA - Alawiyah, Tuti; Parhaini, Lailatul (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2022)
This study aims to improve fine motor skills by playing constructively with Lego for children in Group A of PAUD Raudatul Jannah, Genggelang Village, Gangga District, in the 2020/2021 Academic Year, aged 4-5 years, with a total of 14 children, namely 4 boys and 10 girls. The research method used is the Classroom Action Research Method, which is a research conducted systematically reflective of the various actions taken by the teacher to improve learning conditions. The data in this study were collected using observation methods, interview methods and documentation methods. The results of this study indicate that there is an increase in the fine motor skills of children in group A. In the pre-cycle the average value obtained was 41.2 with classical completeness of 21.4%. In the first cycle the fine motor skills of children increased with an average value of 59.9 and the percentage of classical completeness was 35.7% and in the second cycle the fine motor skills of children increased with an average value of 70 and the percentage of classical completeness reached 85.7%. This shows an increase in the percentage of fine motor skills as much as 64.3% from 21.4% to 85.7%, which means that fine motor skills are in the very well developed criteria with a percentage above 76% already achieved in this study. On average, children experience an increase in fine motor skills by playing constructive lego at PAUD Raudatul Jannah Gitak Demung, Genggelang Village, Gangga District, North Lombok Regency.